Biotransformation of Flavonoid Conjugates with Fatty Acids and Evaluations of Their Functionalities - Sun, Cynthia Q.; Johnson, Keryn D.; Wong, Herbert; Foo, L. Y. (Frontiers in Pharmacology, 2017)
Enzymatic conjugation with fatty acids including Omega-3 polyunsaturated fatty acids (ω-3 PUFA) derived from fish oil to three citrus fruit-derived flavonoids: grapefruit extract, naringin and neohesperidin dihydrochalcone (NHDC) were investigated. The conversions were achieved over 85% under the catalysis of lipase Novozyme 435 in acetone at 45°C at semi-preparative scale. The conjugates were purified via solvent partition and silica gel chromatography and achieved 90%-98% in purity. The NMR analysis of the conjugates confirmed that the fatty acid carbon chain was linked onto the primary –OH group on the glucose moiety of the flavonoids. The purified flavonoid conjugates alongside their original flavonoids were analyzed for antioxidant activities via DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging assay, and anti-peroxidation test via peroxide values measured during a one-week fish oil storage trial. Vascular endothelial growth factor (VEGF) assay was conducted with 1, 10 and 100 µM of the flavonoids and their conjugates, respectively, and total VEGF levels were measured at 24 and 48 hours, respectively using ELISA assay and dot blot analysis. The results from these functionality experiments demonstrated that flavonoid FA conjugates have at least comparable (if not higher) antioxidant activity, anti-peroxidation activity and anti-angiogenic activity.